Challenges in Community Participation in Management of Nature Reserves - Mahlangabeza, Luyolo; Zwelakhe, Loyiso (Mediterranean Journal of Social Sciences, 2021)
The management and protection of protected areas such as nature reserves remains a primary concern for the different stakeholders involved especially the marginalised rural communities that are deprived of genuine ownership of the natural resources. Therefore, the representation of the marginalised rural communities adjacent to the protected areas has become significant in the control and utilisation of natural resources in protected areas. Community Property Associations (CPAs) have been tasked with the mandate to ensure community representation in the management of natural resources. However, their participation in the management of natural resources have been questioned and under scrutiny. The aim of this study is to investigate the challenges in communal participation in management of nature reserves. A qualitative research method was used for collecting data. Semi-structured interviews were utilised to collect data from a sample constituting n=10 respondents. The data were analysed using thematic analysis. The data from this study revealed that there is limited participation by the CPA members in the management of Dwesa-Cwebe Nature Reserve. The ownership and participation in the management of natural resources by local communities is important in ensuring meaningful development. Received: 21 July 2021 / Accepted: 20 September 2021 / Published: 5 November 2021